Decreased serum MMP-9 levels in patients with nontraumatic osteonecrosis of the femoral head - Guopeng Li; Fengxuan Ji; Wenchao Guo; Biaofang Wei (BMC Musculoskeletal Disorders, 2023)
Abstract Background Matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinases-1 (TIMP-1) are involved in the pathological mechanism of osteonecrosis of the femoral head (ONFH). This study aimed to investigate the relationship of serum MMP-9, TIMP-1, and the MMP-9/TIMP-1 ratio with disease severity in patients with nontraumatic ONFH. Methods Serum levels of MMP-9 and TIMP-1 among 102 nontraumatic ONFH patients and 96 healthy individuals were determined by enzyme-linked immunosorbent assay (ELISA). Imaging severity was determined using the FICAT classification system. The Harris hip score (HHS) and visual analogue scale (VAS) were used to evaluate clinical progress. The correlations of serum MMP-9 and TIMP-1 levels with imaging severity and clinical progress was evaluated statistically. The diagnostic value of MMP-9 for NONFH disease severity was evaluated by examining receiver operating characteristic (ROC) curves. Results The serum MMP-9 levels and the MMP-9/TIMP-1 ratio were significantly increased in patients with ONFH compared to normal controls, and TIMP-1 levels did not differ between the two groups. Serum MMP-9 levels and the MMP-9/TIMP-1 ratio were positively correlated with FICAT stage and VAS and were negatively correlated with the HHS score. The ROC curve results indicated that MMP-9 could be used as a potential marker of nontraumatic ONFH imaging progression. Conclusions We hypothesize that increased MMP-9 expression and an imbalance in the MMP-9/TIMP-1 ratio play a role in the development of ONFH and are correlate with the severity of ONFH. The determination of MMP-9 can be a useful tool to assess the severity of the disease in patients with nontraumatic ONFH.